Geology, petrography and geochemistry of Archean granitoids of Sapucaia, Carajás Province, Pará State, Brazil - Teixeira, Mayara Fraeda Barbosa (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Teses